1994
DOI: 10.1046/j.1471-4159.1994.63030886.x
|View full text |Cite
|
Sign up to set email alerts
|

Adrenalectomy Attenuates Kainic Acid‐Induced Spectrin Proteolysis and Heat Shock Protein 70 Induction in Hippocampus and Cortex

Abstract: Glucocorticoids have been shown to exacerbate the damaging effects of a variety of neurotoxic insults in the hippocampus and other brain areas. Evidence suggests that the endangering effects of glucocorticoids may be due to augmenting the cascade of events, such as elevations in intracellular calcium levels, because of excitatory amino acid (EAA) receptor stimulation. A potential mechanism responsible for EAA‐induced neuronal damage is activation of calcium‐sensitive proteases, such as calpain, which then prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…It has been demonstrated that lesioning the ACC disrupts regulation of the HPA system's response to psychological stress in rats (Diorio, Viau, & Meaney, 1993). Evidence suggests that these relations are reciprocal in nature as GCs also affect the functioning of the prefrontal cortex, including the ACC (e.g., Karreman, Moghaddam, 1996;Lowy, 1994). Research involving experimental administration of exogenous GCs to adult human and nonhuman primates indicates that highly elevated levels of GCs interfere with frontal processes, such as inhibitory control, attention regulation, and planning (Kopell, Wittner, Lunde, Warrick, & Edwards, 1970;Lupien, Gillin, & Hauger, 1999;Lyons, Lopez, Yang, & Schatzberg, 2000;Young, Sahakian, Robbins, & Cowen, 1999).…”
mentioning
confidence: 99%
“…It has been demonstrated that lesioning the ACC disrupts regulation of the HPA system's response to psychological stress in rats (Diorio, Viau, & Meaney, 1993). Evidence suggests that these relations are reciprocal in nature as GCs also affect the functioning of the prefrontal cortex, including the ACC (e.g., Karreman, Moghaddam, 1996;Lowy, 1994). Research involving experimental administration of exogenous GCs to adult human and nonhuman primates indicates that highly elevated levels of GCs interfere with frontal processes, such as inhibitory control, attention regulation, and planning (Kopell, Wittner, Lunde, Warrick, & Edwards, 1970;Lupien, Gillin, & Hauger, 1999;Lyons, Lopez, Yang, & Schatzberg, 2000;Young, Sahakian, Robbins, & Cowen, 1999).…”
mentioning
confidence: 99%
“…Although most of this evidence comes from studies conducted on adrenalectomized rats, it suggests that substances or procedures capable of decreasing the level of circulating corticosterone or preventing its excessive release during insults described above may have potential neuroprotective properties. It should be stressed here clearly that insults such as cerebral ischemia or kainic acid seizures induce marked secretion of glucocorticoids (Lowy et al, 1994).…”
Section: Introductionmentioning
confidence: 93%
“…Brain areas engaged in the kainic acid injury show significant changes in cytoskeletal proteins (Elliott et al, 1993;Lowy et al, 1994;Wang et al, 1993) and are marked, among others, by the robust appearance of HSP 70 (Armstrong et al, 1996;Planas et al, 1994;Sanz et al, 1997;Schreiber et al, 1993;Zhang et al, 1996). Considering such a profile of effects, kainic acid is widely used as a convenient tool in experiments studying the pharmacology of epilepsy as well as mechanisms of neurodegeneration associated with this type of seizure (Ben-Ari, 1985).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations